2021
DOI: 10.1101/2021.01.19.21250110
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

External Validations of Cardiovascular Clinical Prediction Models: A Large-scale Review of the Literature

Abstract: BackgroundThere are many clinical prediction models (CPMs) available to inform treatment decisions for patients with cardiovascular disease. However, the extent to which they have been externally tested and how well they generally perform has not been broadly evaluated.MethodsA SCOPUS citation search was run on March 22, 2017 to identify external validations of cardiovascular CPMs in the Tufts PACE CPM Registry. We assessed the extent of external validation, performance heterogeneity across databases, and expl… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 32 publications
(35 reference statements)
1
10
0
Order By: Relevance
“…Our prior literature review 6 was unable to examine calibration because it is frequently unreported and, when reported, the metrics used vary from study to study and are largely uninformative with regard to the magnitude of miscalibration (eg, Hosmer Lemeshow, which yields only a P , which tends to be large in small samples and small in large samples). The validations we performed ourselves revealed that CPM-predicted outcome rates frequently deviate from observed outcome rates even when discrimination was good.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our prior literature review 6 was unable to examine calibration because it is frequently unreported and, when reported, the metrics used vary from study to study and are largely uninformative with regard to the magnitude of miscalibration (eg, Hosmer Lemeshow, which yields only a P , which tends to be large in small samples and small in large samples). The validations we performed ourselves revealed that CPM-predicted outcome rates frequently deviate from observed outcome rates even when discrimination was good.…”
Section: Discussionmentioning
confidence: 99%
“…Most of those that have been externally validated have been evaluated only once. 6,7 Yet, our prior analysis also called into question the value of these single validations, since discriminatory performance typically varies tremendously when a single model is evaluated on multiple databases. 6…”
mentioning
confidence: 99%
“…Relatedness was assessed using relatedness rubrics specifically developed for this purpose. [11] dAUC indicates the change in area under the receiver operator characteristic curve; CI, confidence interval; CPM, clinical prediction model; ROB, risk of bias.…”
Section: Discussionmentioning
confidence: 99%
“…We included validations of each de novo CPM in the CPM Registry, which have been previously identified with a Scopus citation search conducted on March 22, 2017 [11] . An external validation was defined as any model evaluation on a dataset distinct from the derivation data, including validations that were performed on a temporally or geographically distinct part of the same cohort (i.e., nonrandom split sample), that reported at least one measure of model performance (discrimination and/or calibration).…”
Section: External Validationsmentioning
confidence: 99%
See 1 more Smart Citation